Evaluation of the implementation of professional development efforts in improving the professionalism of Geography teachers - Alfin Nuramalia Yuniandita; Mukminan Mukminan (REID (Research and Evaluation in Education), 2020)
This study aims to determine how the implementation of teacher professional development efforts and the government and/or related agencies' participation in supporting teacher professional improvement can formulate sustainable professional development efforts in improving the professionalism of high school geography teachers in Brebes Regency. This evaluation study used the discrepancy model. The method used was descriptive quantitative and analyzed using percentage descriptive techniques. The data in this evaluation study were collected through questionnaires, interviews, and observations. The sample in this study consisted of 30 high school Geography teachers in Brebes Regency, while the sampling technique used was disproportionate stratified random sampling. Regardless of the results of the study that Geography teachers had a good understanding of the duties and obligations that had to be fulfilled as professional teachers, that efforts for sustainable professional development had not been fully implemented properly. The result shows that the Sustainable Professional Development efforts carried out by Geography teachers are in the criteria of “Good Enough” with an average score of 66.83 (out of a maximum score of 120). From several programs supporting the teachers’ professional development, only a few programs are routinely carried out by Geography teachers, including internal coaching by supervisors, Geography subject forum activities, and workshops. Besides, several professional development programs deserve special attention from the government due to the lack of teacher participation, namely apprenticeships, short courses, distance learning, level training, and further education, given that some of these programs provide opportunities for teachers to update and develop their knowledge.